A liturgy of grief : a pastoral commentary on Lamentations - Allen, Leslie C. (Grand Rapids, Mich. : Baker Academic, 2011)
Allen, an experienced scholar and hospital chaplain, is the first to use the Old Testament book of Lamentations to throw light on grief, and to use contemproray examples and discussions of grief to throw lights on Lamentations.
Foreword / Nichols Wolterstorff -- First poem (Lamentations 1) : grief, guilt, and the need for prayer (1) -- Second prayer (Lamentations 2) : grief, guilt, and the need for prayer (2) -- Third poem (Lamentations 3) : the wounded healer -- Fourth poem (Lamentations 4) : grief and guilt -- 5. Fifth poem (Lamentations 5) : the congregation's prayer as a turning point.
Includes bibliographical references (p. 180-190) and index.
Keywords: Bible. -- Commentaries; Grief -- Religious aspects -- Christianity; Pastoral care